Evaluating social media: towards a practical model for measuring social media influence - Hassan, Shahizan; Shiratuddin, Norshuhada; Hashim, Nor Laily; Li, Feng (2014)
Despite the widespread adoption and popularity of social media, research on measuring the quantifiable impact of popular social media platforms remains scarce.To this end, this study attempts to investigate how the influence of social media can be assessed in quantitative terms. The main objective is to develop a new assessment model able to integrate a broad range of criteria such as likes, subscribers, comments, posts, shares, and links.The authors extend previous assessment models focused on individual platforms such as blogs and propose a Social Media Influence Assessment model (SMIA).The process of model development—criteria, dimensions, and formula—and its validation are discussed.The results indicate that social media's influence can be measured in a structured, quantifiable manner by utilising a set of nine criteria grouped into three dimensions: recognition, activity generation, and credibility.